Assessment of clinical outcomes in patients with post-traumatic stress disorder: analysis from the UK Medical Cannabis Registry. (2nd November 2022) - Pillai, Manaswini; Erridge, Simon; Bapir, Lara; Nicholas, Martha; Dalavaye, Nishaanth; Holvey, Carl; Coomber, Ross; Barros, Daniela; Bhoskar, Urmila; Mwimba, Gracia; Praveen, Kavita; Symeon, Chris; et al.
ABSTRACT: Background: The current paucity of clinical evidence limits the use of cannabis-based medicinal products (CBMPs) in post-traumatic stress disorder (PTSD). This study investigates health-related quality of life (HRQoL) changes and adverse events in patients prescribed CBMPs for PTSD. Methods: A case-series of patients from the UK Medical Cannabis Registry was analyzed. HRQoL was assessed at 1-, 3-, and 6-months using validated patient reported outcome measures (PROMs). Adverse events were analyzed according to the Common Terminology Criteria for Adverse Events version 4.0. Statistical significance was defined as p < 0.050. Results: Of 162 included patients, 88.89% (n = 144) were current/previous cannabis users. Median daily CBMP dosages were 5.00 (IQR: 0.00–70.00) mg of cannabidiol and 145.00 (IQR: 100.00–200.00) mg of Δ9-tetrahydrocannabinol. Significant improvements were observed in PTSD symptoms, sleep, and anxiety across all follow-up periods (p < 0.050). There were 220 (135.8%) adverse events reported by 33 patients (20.37%), with the majority graded mild or moderate in severity (n = 190, 117.28%). Insomnia and fatigue had the greatest incidence (n = 20, 12.35%). Conclusions: Associated improvements in HRQoL were observed in patients who initiated CBMP therapy. Adverse events analysis suggests acceptability and safety up to 6 months. This study may inform randomized placebo-controlled trials, required to confirm causality and determine optimal dosing.